Cured products and electronic components
Patent Information
- Application Number
- JP2026052157
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-26
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 本発明の一態様によれば、シリコーン樹脂の硬化阻害を抑制可能な硬化物を提供することができる。
Smart Images

Figure 2026167583000001 
Figure 2026167583000002 
Figure 2026167583000003
Abstract
Description
[Technical Field]
[0001] This invention relates to cured products and electronic components. [Background technology]
[0002] A light-emitting device is known in which light-emitting elements such as light-emitting diodes (LEDs) are mounted on a printed circuit board on which a highly reflective solder resist has been formed, and the light-emitting elements are coated with silicone resin. As a resin composition for forming solder resist, for example, Patent Document 1 describes a photosensitive thermosetting resin composition comprising an alkoxy group-containing silane-modified epoxy resin, an unsaturated group-containing polycarboxylic acid resin, a diluent, a photopolymerization initiator, and a curing adhesion imparter. Patent Document 2 describes a white alkali-developable photocurable / thermosetting solder resist composition comprising a carboxyl group-containing (meth)acrylate (meth)acrylic compound without an aromatic ring, a photopolymerization initiator, an epoxy compound, a curing agent for thermosetting, a curing catalyst for thermosetting, an inorganic powder, and an organic solvent. Patent Document 3 describes a flame-retardant solder resist composition comprising a carboxyl group-containing photosensitive resin, an acrylic urethane resin, a photopolymerization initiator, a diluent, an epoxy compound, and a phosphorus-containing organic filler. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2007-249148 [Patent Document 2] Japanese Patent Publication No. 2009-194222 [Patent Document 3] International Publication No. 2011 / 062053 [Overview of the project] [Problems that the invention aims to solve]
[0004] In order to increase the reflectivity of solder resist in light-emitting devices, increasing the content of white pigment (e.g., titanium dioxide) or increasing the film thickness may reduce the curability of the bottom layer. To compensate for this, the amount of photopolymerization initiator added was sometimes increased. However, increasing the amount of photopolymerization initiator added may reduce the curability of the silicone resin used to coat the light-emitting element. Therefore, for example, the cured solder resist was sometimes washed with a solvent to remove the photopolymerization initiator or its decomposition products beforehand. However, in the case of cured products of resin compositions described in Patent Documents 1 or 2, for example, there is a concern that the solvent may not penetrate the cured product sufficiently, and that the photopolymerization initiator or its decomposition products may not be sufficiently removed. Furthermore, in the case of cured products of solder resist compositions described in Patent Document 3, excessive solvent penetration may lead to a large change in hardness before and after solvent immersion, raising concerns that the cured product may peel off during thermal cycling tests.
[0005] One aspect of the present invention aims to provide a cured product capable of suppressing curing inhibition of silicone resin. [Means for solving the problem]
[0006] The specific means for solving the aforementioned problems are as follows, and the present invention encompasses the following embodiments.
[0007] [1] A cured product formed from a curable resin composition comprising a carboxyl group-containing urethane resin, a first photopolymerization initiator containing a phosphorus atom, an epoxy compound, and titanium dioxide, wherein the ratio G2 / G1 of the elastic modulus G1 of the heat-treated cured product obtained by heat-treating the cured product at 280°C for 5 minutes, as measured by dynamic viscoelasticity at 25°C, to the elastic modulus G2 of the washed cured product obtained by immersing the heat-treated cured product in propylene glycol monomethyl ether at 25°C for 5 minutes and then drying, is 1.05 or more and 1.20 or less.
[0008] [2] The cured product according to [1], wherein the concentration of the first photopolymerization initiator in acetonitrile extracted from 50 mg of the heat-treated cured product into 10 mL of acetonitrile at 25°C for 10 minutes is 0.1 ppm or more and 30 ppm or less.
[0009] [3] The carboxyl group-containing urethane resin is a cured product according to [1] or [2], comprising a polycarbonate skeleton.
[0010] [4] The curable resin composition comprises a first photopolymerization initiator containing an acylphosphine oxide-based photopolymerization initiator and a second photopolymerization initiator containing at least one selected from the group consisting of oxime ester-based photopolymerization initiators and titanocene-based photopolymerization initiators, as described in any one of [1] to [3].
[0011] [5] The epoxy compound is a cured product according to any one of [1] to [4], wherein the epoxy equivalent is 400 g / eq. or more and 1000 g / eq. or less.
[0012] [6] The cured product according to any one of [1] to [5], wherein the titanium oxide content is 65% by mass or more.
[0013] [7] An electronic component comprising a cured product as described in any of [1] to [6]. [Effects of the Invention]
[0014] According to one aspect of the present invention, it is possible to provide a cured product that can suppress curing inhibition of silicone resin. [Modes for carrying out the invention]
[0015] In the present specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of that process is achieved. In addition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified, when a plurality of substances corresponding to each component are present in the composition. Further, the upper and lower limits of the numerical ranges described in the present specification can be arbitrarily selected and combined from the numerical values exemplified as the numerical ranges. In the present specification, "(meth)acrylate" is a general term referring to acrylate, methacrylate and mixtures thereof, and the same applies to other similar expressions. The solid content means the residue obtained by removing volatile components (for example, organic solvents) from the composition or its components. The weight average molecular weight and number average molecular weight are determined as standard polystyrene equivalent values measured by gel permeation chromatography (GPC). The GPC measurement is performed using tetrahydrofuran as an eluent and an RI detector. Hereinafter, embodiments of the present invention will be described in detail. However, the embodiments described below are illustrative of cured products and electronic components for embodying the technical idea of the present invention, and the present invention is not limited to the following cured products and electronic components.
[0016] Cured product The cured product is formed from a curable resin composition comprising a carboxy group-containing urethane resin, a first photopolymerization initiator containing a phosphorus atom (hereinafter sometimes simply referred to as the photopolymerization initiator), an epoxy compound, and titanium oxide. A cured product formed from a specific curable resin composition, by being in a state exhibiting a predetermined elastic modulus ratio, can suppress curing inhibition of the silicone resin used for coating the cured product. Here, the predetermined elastic modulus ratio is calculated as the elastic modulus ratio G2 / G1, where G1 is the elastic modulus at 25°C measured by dynamic viscoelasticity measurement of the heat-treated cured product obtained by heat-treating the cured product at 280°C for 5 minutes, and G2 is the elastic modulus at 25°C measured by dynamic viscoelasticity measurement of the washed cured product obtained by immersing the heat-treated cured product in propylene glycol monomethyl ether at 25°C for 5 minutes and then drying it. The elastic modulus ratio G2 / G1 may be, for example, 1.05 or more and 1.20 or less, preferably 1.10 or more, or 1.12 or more, and may be 1.18 or less, or 1.15 or less. When the elastic modulus ratio G2 / G1 is within the above range, curing inhibition of the silicone resin to be coated tends to be suppressed.
[0017] That the ratio of the elastic modulus G2 after solvent immersion to the elastic modulus G1 before solvent immersion in the cured product falls within a predetermined range is considered to mean, for example, that the content of a substance that causes curing inhibition of the silicone resin and can be eluted into the solvent (for example, a photopolymerization initiator or a decomposition product thereof) is low, and that the amount of solvent absorbed by the cured product accompanying solvent immersion is small, the cured product is in a state where it is difficult to swell excessively, and the substance that causes curing inhibition of the silicone resin is in a state where migration is unlikely to occur. It is considered that with a cured product in such a state, curing inhibition of the silicone resin is suppressed when coated with the silicone resin. In addition, since the cured product has flexibility, the occurrence of corner cracks is effectively suppressed even after a thermal cycle. This can be considered, for example, because the curable resin composition contains a carboxy group-containing urethane resin and titanium oxide. In one aspect, the carboxy group-containing urethane resin may contain a polycarbonate skeleton. It is considered that when the carboxy group-containing urethane resin contains a polycarbonate skeleton, the flexibility is further improved, and the occurrence of corner cracks is more effectively suppressed.
[0018] Here, a corner crack in a cured material refers to a crack that runs from the corner of an opening in the cured material. The occurrence of cracks in a portion of the cured material can lead to insufficient circuit protection and a decrease in insulation reliability. Furthermore, cracks can allow moisture to penetrate the cured material more easily, potentially causing delamination.
[0019] The elastic modulus ratio G2 / G1 is evaluated based on the elastic modulus G1 of the cured product after heat curing treatment. The elastic modulus G1 is measured for a post-heat-treated cured product obtained by performing an additional heat treatment at 280°C for 5 minutes on a cured product obtained under normal conditions (e.g., exposure, development, and heat curing). The elastic modulus is measured at 25°C using a dynamic viscoelasticity measuring device (e.g., RSA-G2 manufactured by T.A. Instrument Japan Co., Ltd.). The elastic modulus G1 of the post-heat-treated cured product at 25°C may be, for example, 3.0 GPa or more and 5.5 GPa or less, preferably 4.0 GPa or more, or 4.4 GPa or more, and may be 5.0 GPa or less, or 4.8 GPa or less. When the elastic modulus G1 of the post-heat-treated cured product at 25°C is within the above range, there is a tendency for photopolymerization initiators and the like remaining in the coating film to be removed more easily by propylene glycol monomethyl ether.
[0020] The elastic modulus G2 of the cured product after solvent immersion is measured in the same manner as above for the washed cured product obtained by immersing the heat-treated cured product in propylene glycol monomethyl ether (hereinafter also referred to as the solvent) at 25°C for 5 minutes and then drying it. The purity of the propylene glycol monomethyl ether used for immersion may be, for example, 99% or higher. The propylene glycol monomethyl ether may also contain isomers. The amount of solvent used for immersion may be, for example, 10 to 1000 times the volume of the cured product. Drying of the cured product after immersion in the solvent is sufficient to remove the solvent adhering to the cured product, for example, by a solvent removal treatment at 40°C for 10 minutes. The elastic modulus G2 of the washed cured product at 25°C may be, for example, 3.2 GPa or more and 5.7 GPa or less, preferably 4.2 GPa or more, 4.8 GPa or more, or 5.0 GPa or more, 5.6 GPa or less, or 5.4 GPa or less. When the elastic modulus G2 of the hardened material after washing is within the aforementioned range at 25°C, the occurrence of corner cracks tends to be further suppressed.
[0021] Furthermore, the elastic modulus G0 of the cured product before the additional heat treatment at 280°C for 5 minutes, measured in the same manner as above, may be, for example, 3.0 GPa or more and 5.5 GPa or less, preferably 4.0 GPa or more, or 4.2 GPa or more, or 5.0 GPa or less, or 4.8 GPa or less. When the elastic modulus G0 of the cured product before heat treatment at 25°C is within the above range, excessive swelling tends to be avoided when the cured product after the additional heating at 280°C for 5 minutes is immersed in a solvent. In addition, the ratio G0 / G1 of the elastic modulus G0 of the cured product before heat treatment to the elastic modulus G1 of the cured product after heat treatment may be, for example, 0.90 or more and 1.00 or less, preferably 0.93 or more, or 0.97 or less. When the ratio G0 / G1 is within the above range, there is a tendency for photopolymerization initiators and the like to be sufficiently removed from the cured coating film after solvent immersion.
[0022] The elastic modulus of the cured product can be adjusted to a desired range by adjusting the composition of the curable resin composition that forms the cured product. For example, increasing the amount of epoxy compound with an epoxy equivalent of 1000 g / eq. or less can increase the elastic modulus G1 of the heat-treated cured product. For example, increasing the amount of compound having a photopolymerizable group can increase the elastic modulus G2 of the washed cured product. Furthermore, by adjusting the amount of epoxy compound added (for example, from 1% to 20% by mass relative to the curable resin composition), the elastic modulus ratio G2 / G1 can be easily adjusted to a range of 1.05 to 1.20.
[0023] The heat-treated cured product may contain unreacted photopolymerization initiators. The photopolymerization initiator content in the heat-treated cured product can be evaluated, for example, as follows: Take a 50 mg sample from the heat-treated cured product. The sample may be in powder form, for example. Immerse the prepared sample in 10 mL of acetonitrile and perform an extraction treatment at 25°C for 10 minutes. The extraction treatment is performed, for example, by ultrasonic irradiation. The frequency of the ultrasound used may be, for example, 10 kHz to 50 kHz, preferably 20 kHz or higher, or 40 kHz or lower. The output of the ultrasound may be, for example, 50 W to 300 W, preferably 100 W or higher, or 200 W or lower. Next, filter the sample and measure the photopolymerization initiator content in the filtered acetonitrile using high-performance liquid chromatography (e.g., LC-MS). This allows evaluation of the photopolymerization initiator content in the heat-treated cured product. The purity of the acetonitrile used for extraction may be, for example, 99% or higher.
[0024] The concentration of the photopolymerization initiator extracted from 50 mg of heat-cured product into 10 mL of acetonitrile at 25°C for 10 minutes may be, for example, 0.1 ppm to 30 ppm, preferably 2 ppm or more, or 3 ppm or more, and may be 20 ppm or less, 16 ppm or less, or 13 ppm or less. When the amount of photopolymerization initiator extracted from the heat-cured product is below a predetermined value, the curing inhibition of the silicone resin coating tends to be suppressed more effectively.
[0025] The cured product can exhibit high reflectivity by containing titanium dioxide. The reflectivity of the cured product may be, for example, 50% or more, preferably 70% or more, or 80% or more, as an average reflectivity in the wavelength range of 400 nm to 500 nm. The average reflectivity may also be, for example, less than 100% or 99% or less. The average reflectivity is calculated as the arithmetic mean of the reflectivity for every 1 nm. The cured product is useful, for example, as a solder resist used in electronic components, and is particularly useful as a solder resist and light-reflective solder resist used in light-emitting devices that include a printed circuit board and a light-emitting element (e.g., a light-emitting diode (LED)) placed on the printed circuit board. The LED mounting substrate used in the light-emitting device may have a base material and a cured product film placed on the base material. The cured product film may have an opening for mounting the LED. The shape of the opening for mounting the LED may be rectangular, approximately rectangular, circular, approximately circular, elliptical, approximately elliptical, etc. The perimeter of the opening may be, for example, 200 μm or more and 4 mm or less.
[0026] A cured product can be formed by curing a curable resin composition, as described later, under predetermined conditions depending on the curable resin composition. For example, a cured product can be formed by placing a resin layer formed from the curable resin composition on a substrate and curing the resin layer by a pattern forming method as described below. The resin layer may be, for example, a dried coating film of the curable resin composition. The pattern forming method may include, for example, an exposure step, a development step, and the curing step.
[0027] As substrates on which the resin layer is placed, pre-circuited printed circuit boards, flexible printed circuit boards, paper-phenolic resin, paper-epoxy resin, glass cloth-epoxy resin, glass-polyimide, glass cloth / nonwoven fabric-epoxy resin, glass cloth / paper-epoxy resin, synthetic fiber-epoxy resin, copper-clad laminates using composite materials such as fluororesin, polyethylene, PPO, and cyanate ester, glass substrates, ceramic substrates, and wafers can be used. Films such as polyimide film and polyethylene terephthalate film can also be used as substrates.
[0028] The resin layer is formed by applying a curable resin composition onto a substrate. The curable resin composition can be applied by methods such as screen printing, roll coating, spin coating, spray coating, dispensing, dip coating, or curtain coating. The applied curable resin composition is then dried and placed on the substrate as a resin layer, after removing any solvents as needed. When the resin layer is placed using a dry film, as described later, the resin layer can be placed on the substrate by bonding the resin layer of the dry film to the substrate. For bonding the resin layer to the substrate, it is sufficient that the substrate and the resin layer of the dry film are in close contact, and there are no particular limitations, but it is preferable to bond them under pressure and heat using a vacuum laminator or the like. By using such a vacuum laminator, the resin layer adheres closely to the circuit board, preventing the inclusion of air bubbles and improving the ability to fill holes in the substrate surface. The pressure conditions may be, for example, 0.1 MPa to 2.0 MPa, and the heating conditions may be, for example, 40°C to 120°C.
[0029] In the exposure process, the resin layer is exposed (irradiated with active energy rays). If a first dry film is laminated on the resin layer, exposure can be performed from above the first film. In this process, only the exposed resin layer hardens. The exposure process is not particularly limited; for example, it may be selectively exposed with active energy rays through a photomask with a desired pattern formed on it using a contact (or non-contact) method, or the desired pattern may be exposed with active energy rays using a direct writing device.
[0030] The exposure machine used for active energy ray irradiation can be any device equipped with a high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, etc., that irradiates ultraviolet light with an emission peak wavelength in the range of 350 nm to 450 nm. Furthermore, a direct writing device (for example, a laser direct imaging device that directly draws images with a laser using CAD data from a computer) can also be used. As the laser light source for the direct writing device, either a gas laser or a solid-state laser is acceptable, as long as the laser light has an emission peak wavelength in the range of 350 nm to 410 nm. The exposure amount for image formation varies depending on the film thickness, etc., but is generally 20 mJ / cm². 2 More than 800mJ / cm 2 Preferably 20 mJ / cm² 2 More than 600mJ / cm 2 The following range is possible. Furthermore, exposure may be by parallel light or scattered light.
[0031] In the development process, the first film is peeled off as needed, and then the exposed resin layer is developed to form a patterned cured resin layer on the substrate. The development process is not particularly limited and can be carried out by dipping, showering, spraying, brushing, etc. Alkaline aqueous solutions such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, and amines can be used as the developer.
[0032] Next, the patterned cured resin layer is cured by irradiation with active energy rays (light) or heat to form a cured product. This process is called main curing or additional curing, and it promotes the polymerization of unreacted monomers in the exposed cured resin layer, and further, it can thermally cure the carboxyl group-containing urethane resin and the epoxy compound, which is a thermosetting component, thereby reducing the amount of remaining carboxyl groups. Irradiation with active energy rays can be carried out in the same manner as the exposure described above, but it is preferable to carry it out under conditions with a stronger irradiation energy than that used during exposure. For example, 500 mJ / cm². 2 More than 3000mJ / cm 2 The following conditions may be met. Furthermore, thermal curing can be carried out under heating conditions of 100°C to 200°C for approximately 20 to 90 minutes. It is preferable to perform thermal curing after photocuring. Performing photocuring first suppresses the flow of the resin even during thermal curing.
[0033] Curable resin composition The curable resin composition that forms the cured product may contain a carboxyl group-containing urethane resin, a first photopolymerization initiator containing a phosphorus atom, an epoxy compound, and titanium dioxide, and may further contain other components as needed.
[0034] The curable resin composition may contain at least one carboxyl group-containing urethane resin. The inclusion of a carboxyl group-containing urethane resin makes the curable resin composition alkali-developable. From the viewpoint of photocurability, the carboxyl group-containing urethane resin preferably has an ethylenically unsaturated double bond in addition to the carboxyl group within its molecule. The curable resin composition may also contain a carboxyl group-containing urethane resin without an ethylenically unsaturated double bond and a photopolymerizable compound. Examples of photopolymerizable compounds include compounds having an ethylenically unsaturated double bond, and may be compounds derived from acrylic acid, methacrylic acid, or their derivatives.
[0035] Specific examples of carboxyl group-containing urethane resins include the following compounds (which may be either oligomers or polymers):
[0036] (1) A carboxyl group-containing urethane resin obtained by polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0037] (2) Diisocyanates reacted with bifunctional epoxy resins such as bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bixylenol type epoxy resin, and biphenol type epoxy resin, and monocarboxylic acid compounds having ethylenically unsaturated double bonds such as (meth)acrylic acid. Partially acid anhydride modified products, carboxyl group-containing dialcohol compounds, and diol compounds are obtained by polyaddition reactions of these products with these compounds.
[0038] (3) A carboxyl group-containing urethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as hydroxyalkyl (meth)acrylate, during the synthesis of the resin described in (1) or (2) above, and then (meth)acrylicating the terminal (meth) resin.
[0039] (4) A carboxyl group-containing urethane resin in which a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule is added to the synthesis of the resin of (1) or (2) above, and the terminal (meth)acrylic compound is formed by adding such a compound to the end (meth)acrylic compound, such as an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate.
[0040] (5) A carboxyl group-containing urethane resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to any of the resins described in (1) to (4).
[0041] The acid value of the carboxyl group-containing urethane resin may be, for example, 5 mg KOH / g or more and 150 mg KOH / g or less. When the acid value of the carboxyl group-containing urethane resin is 5 mg KOH / g or higher, the developability is further improved. Furthermore, when the acid value is 150 mg KOH / g or less, the resolution is further improved. Preferably, the acid value of the carboxyl group-containing urethane resin may be 10 mg KOH / g or more and 130 mg KOH / g or less. Note that the acid value of the carboxyl group-containing urethane resin is a value measured in accordance with JIS K5601-1-2-1:1999.
[0042] The weight-average molecular weight of the carboxyl group-containing urethane resin varies depending on the resin skeleton, but may be, for example, 2,000 to 150,000. A weight-average molecular weight of 2,000 or more can further improve the touch-drying properties and resolution of the coated film. Furthermore, a weight-average molecular weight of 150,000 or less can further improve developability and storage stability. Preferably, the weight-average molecular weight of the carboxyl group-containing urethane resin may be 5,000 to 100,000.
[0043] By including a carboxyl group-containing urethane resin in the curable resin composition, the dispersibility and reflectivity of the curable resin composition, as well as the insulation reliability of the cured product, can be further improved. Furthermore, the adhesion of the cured product to the substrate and the warping of the substrate caused by the application of the cured product can be reduced. In particular, a carboxyl group-containing urethane resin that does not have an aromatic ring is preferred as the carboxyl group-containing urethane resin.
[0044] As a carboxyl group-containing urethane resin that does not have an aromatic ring, a carboxyl group-containing urethane resin obtained by reacting (a) an aliphatic compound having two or more isocyanate groups in one molecule, (b) a carboxyl group-containing aliphatic dialcohol, (c) an aliphatic diol having two or more alcoholic hydroxyl groups in one molecule but not a carboxyl group, and (d) a monohydroxy(meth)acrylate compound is preferred, and a carboxyl group-containing urethane resin containing a polycarbonate skeleton is more preferred. Specific examples of compounds (a) to (d) are given below, but the compounds (a) to (d) are not limited to the following example compounds. Furthermore, each of compounds (a) to (d) may be used alone or in combination of two or more.
[0045] (a) Examples of aliphatic compounds having two or more isocyanate groups in one molecule include isophorone diisocyanate, hexamethylene diisocyanate, cyclohexane-1,3-dimethylene diisocyanate, and cyclohexane-1,4-dimethylene diisocyanate.
[0046] (b) Examples of carboxyl group-containing aliphatic diols include dimethylolpropionic acid and dimethylolbutanoic acid.
[0047] (c) As an aliphatic diol having two or more alcoholic hydroxyl groups in one molecule and no carboxyl group, polycarbonate diols containing repeating units derived from aliphatic diols as constituent units are preferred, for example, polycarbonate diols derived from 1,6-hexanediol, polycarbonate diols derived from 1,5-pentanediol and 1,6-hexanediol, polycarbonate diols derived from 1,4-butanediol and 1,6-hexanediol, and polycarbonate diols derived from 3-methyl-1,5-pentanediol and 1,6-hexanediol.
[0048] (d) Monohydroxy(meth)acrylate compounds serve as end-sealing agents during the polymerization reaction of polyurethane, and examples include hydroxymethyl(meth)acrylate, hydroxyethyl(meth)acrylate, and hydroxybutyl(meth)acrylate.
[0049] The content of carboxyl group-containing urethane resin in the curable resin composition may be, for example, 3% by mass or more and 60% by mass or less on a solid content basis, preferably 5% by mass or more, or 10% by mass or more, and preferably 55% by mass or less, or 30% by mass or less. When the content is 3% by mass or more, the strength of the cured product is further improved. When the content is 60% by mass or less, the viscosity becomes appropriate and the adhesion of the photosensitive resin layer is further improved.
[0050] The curable resin composition may further contain, in addition to the carboxyl group-containing urethane resin, a carboxyl group-containing resin that does not contain urethane bonds (hereinafter also referred to as the second carboxyl group-containing resin). Examples of the second carboxyl group-containing resin include the following compounds.
[0051] (6) Carboxylate-containing resins obtained by copolymerization of an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, or isobutylene.
[0052] (7) A carboxyl group-containing resin obtained by reacting a bifunctional or polyfunctional epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride to the hydroxyl groups present in the side chain.
[0053] (8) A carboxyl group-containing resin obtained by reacting a polyfunctional epoxy resin, in which the hydroxyl groups of a bifunctional epoxy resin are further epoxidized with epichlorohydrin, with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups.
[0054] (9) A carboxyl group-containing polyester resin obtained by reacting a bifunctional oxetane resin with dicarboxylic acids such as adipic acid, phthalic acid, and hexahydrophthalic acid, and adding dibasic acid anhydrides such as phthalic anhydride, tetrahydrophthalic anhydride, and hexahydrophthalic anhydride to the resulting primary hydroxyl groups.
[0055] (10) A carboxyl group-containing resin obtained by reacting an epoxy compound having multiple epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenethyl alcohol, and an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and then reacting the alcoholic hydroxyl group of the reaction product with a polybasic acid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or adipic anhydride.
[0056] (11) A carboxyl group-containing resin obtained by reacting a reaction product obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.
[0057] (12) A carboxyl group-containing resin obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the reaction product with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.
[0058] (13) A carboxyl group-containing resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to any of the resins described in (6) to (12).
[0059] The acid value of the second carboxyl group-containing resin may be, for example, 5 mg KOH / g or more and 150 mg KOH / g or less. If the acid value of the second carboxyl group-containing resin is 5 mg KOH / g or more, the developability is further improved. Also, if the acid value is 150 mg KOH / g or less, the resolution is further improved. Preferably, the acid value of the second carboxyl group-containing resin may be 10 mg KOH / g or more and 130 mg KOH / g or less.
[0060] The weight-average molecular weight of the second carboxyl group-containing resin varies depending on the resin skeleton, but may be, for example, 2,000 to 150,000. A weight-average molecular weight of 2,000 or more can further improve the touch-drying properties and resolution of the coated film. Furthermore, a weight-average molecular weight of 150,000 or less can further improve developability and storage stability. The weight-average molecular weight of the second carboxyl group-containing resin is preferably 5,000 to 100,000.
[0061] When the curable resin composition contains a second carboxyl group-containing resin, the amount of the second carboxyl group-containing resin may be, for example, 5 to 95 parts by mass on a solid content basis, per 100 parts by mass of the total amount of the carboxyl group-containing urethane resin and the second carboxyl group-containing resin, preferably in the proportion of 60 parts by mass or less, 40 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. In one embodiment, the curable resin composition may not contain a second carboxyl group-containing resin.
[0062] The curable resin composition may contain at least one first photopolymerization initiator containing a phosphorus atom. Examples of first photopolymerization initiators containing a phosphorus atom include acylphosphine oxide-based photopolymerization initiators and acylphosphinenate-based photopolymerization initiators, and may contain at least an acylphosphine oxide-based photopolymerization initiator. Acylphosphine oxide-based photopolymerization initiators include bisacylphosphine oxide-based photopolymerization initiators and monoacylphosphine oxide-based photopolymerization initiators. Examples of bisacylphosphine oxide-based photopolymerization initiators include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Examples of monoacylphosphine oxide-based photopolymerization initiators include 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine methyl ester, 2-methylbenzoyldiphenylphosphine oxide, isopropyl pivaloylphenylphosphine ester, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. Examples of acylphosphinate-based photopolymerization initiators include ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate. Photopolymerization initiators containing a phosphorus atom may be used alone or in combination of two or more.
[0063] The first photopolymerization initiator containing a phosphorus atom may have a structure represented by, for example, the following formula (I).
[0064]
Chemical Formula
[0065] In the formula, Ar represents an optionally substituted aryl group. R 1 represents an optionally substituted arylcarbonyl group, or an optionally substituted aryl group. R 2 represents an optionally substituted aryl group, an optionally substituted alkyl group, or an optionally substituted alkyloxy group.
[0066] The aryl group moiety in Ar, R 1 and R 2 may be, for example, a phenyl group or a naphthyl group. Examples of the substituent on the aryl group moiety include alkyl groups having 1 to 3 carbon atoms, alkoxy groups having 1 to 3 carbon atoms, halogen atoms, and the like. The alkyl group moiety in R 2 may be a linear or branched alkyl group having 1 to 18 carbon atoms. Examples of the substituent on the alkyl group moiety include optionally substituted alkoxy groups having 1 to 3 carbon atoms, halogen atoms, and the like.
[0067] The content of the first photopolymerization initiator containing a phosphorus atom in the curable resin composition may be, for example, 1 part by mass or more and 30 parts by mass or less, preferably 2 parts by mass or more and 25 parts by mass or less, may be 4 parts by mass or more, or 6 parts by mass or more, and may be 15 parts by mass or less, or 12 parts by mass or less, relative to 100 parts by mass of the total amount of the carboxy group-containing urethane resin. When the content falls within the above range, the curability of the curable resin composition is improved, and the resolution is further enhanced.
[0068] Furthermore, the content of the first photopolymerization initiator containing phosphorus atoms in the curable resin composition may be 0.1% by mass or more and 5% by mass or less, preferably 0.3% by mass or more, 0.6% by mass or more, or 1% by mass or more, and may be 3% by mass or less, 2.4% by mass or less, or 1.8% by mass or less, based on the total solid content of the curable resin composition. If the content is within the above range, the curability of the curable resin composition will be improved and the resolution will be even better.
[0069] The curable resin composition may further contain at least one photopolymerization initiator that does not contain a phosphorus atom (also called a second photopolymerization initiator) in addition to a photopolymerization initiator containing a phosphorus atom. Examples of second photopolymerization initiators include hydroxyacetophenones, benzoins, benzoin alkyl ethers, benzophenones, acetophenones, thioxanthones, anthraquinones, ketals, benzoic acid esters, oxime esters, titanocenes, and the like. The second photopolymerization initiator may contain at least one selected from the group consisting of oxime esters and titanocenes. That is, the curable resin composition may contain a first photopolymerization initiator containing a phosphorus atom and a second photopolymerization initiator containing at least one selected from the group consisting of oxime ester-based photopolymerization initiators and titanocene-based photopolymerization initiators, and preferably may contain an acylphosphine oxide-based photopolymerization initiator and at least one selected from the group consisting of oxime ester-based photopolymerization initiators and titanocene-based photopolymerization initiators. By further including a specific second photopolymerization initiator in addition to the first photopolymerization initiator containing phosphorus atoms, the curability of the curable resin composition tends to be further improved, and its adhesion to the substrate tends to be further improved.
[0070] Examples of hydroxyacetophenones include 1-hydroxycyclohexylphenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one. Examples of benzoins and benzoin alkyl ethers include benzoin, benzyl, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, and benzoin n-butyl ether. Examples of benzophenones include benzophenone, p-methylbenzophenone, Michla's ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, and 4,4'-bisdiethylaminobenzophenone. Examples of acetophenones include acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl)]-1-[4-(4-morpholinyl)phenyl]-1-butanone, and N,N-dimethylaminoacetophenone. Examples of thioxanthones include thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, and 2,4-diisopropylthioxanthone. Examples of anthraquinones include anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, and 2-aminoanthraquinone.Examples of ketals include acetophenone dimethyl ketal and benzyl dimethyl ketal. Examples of benzoic acid esters include ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoate ethyl ester.
[0071] Oxime esters include 1-[4-(phenylsulfanyl)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 1-{4-[4-(2-hydroxyethoxy)phenylsulfanyl]phenyl}propane-1,2-dione 2-(O-acetyl oxime), 2-(acetyloxyiminomethyl)thioxanthene-9-one, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylmethoxybenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 1-[9-ethyl-6-{2-methyl-4-(2,2- Examples include dimethyl-1,3-dioxolanyl)methoxybenzoyl}-9H-carbazole-3-yl]ethanone 1-(O-acetyloxime), 1-[4-[3-[4-[[2-(acetyloxy)ethyl]sulfonyl]-2-methylbenzoyl]-6-[1-[(acetyloxy)imino]ethyl]-9H-carbazole]-9-yl]phenyloctanone 1-(O-acetyloxime), 3-cyclopentyl-1-[4-(phenylthio)phenyl]-1,2-propanedione 2-(O-benzoyloxime), and 3-cyclopentyl-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1,2-propanedione 2-(O-benzoyloxime).
[0072] Oxime esters may be photopolymerization initiators having a structure in which the substructure represented by formula (II) below is substituted with a compound selected from the group consisting of diarylsulfan, 9H-carbazole, thioxanthene-9-one, fluorene, naphthalene, naphthoquinone, anthracene, anthraquinone, indanedione, coumarin, indole, phenothiazine, thiophene, pyridine, pyrimidine, triphenylamine and derivatives thereof.
[0073] [ka]
[0074] In the formula, R 3 R represents a hydrogen atom, an optionally substituted phenyl group, an optionally substituted C1 to C20 alkyl group, a C5 to C8 cycloalkyl group, a C2 to C20 alkanoyl group, or an optionally substituted benzoyl group. 4 This represents a phenyl group which may have substituents, an alkyl group having 1 to 20 carbon atoms which may have substituents, a cycloalkyl group having 5 to 8 carbon atoms which may have substituents, an alkanoyl group having 2 to 20 carbon atoms which may have substituents, or a benzoyl group which may have substituents.
[0075] Commercially available oxime esters include ADEKA Arcules NCI-700, ADEKA Arcules NCI-730, ADEKA Arcules NCI-831, ADEKA Arcules NCI-930; 1-4-[[4-(2-hydroxyethoxy)phenyl]thio]phenyl]-1,2-propanedione 2-(O-acetyloxime) (all manufactured by ADEKA Corporation), DFI-020, DFI-091 (both manufactured by Daito Chemix Co., Ltd.), CGI-325, Irgacure OXE01, Irgacure OXE02; 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyloxime), Irgacure OXE03, Irgacure OXE04 (all manufactured by BASF Japan Ltd.), etc.
[0076] As for titanocenes, di(η) 5 Examples include -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium and di(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1H-pyrrole-1-yl)ethyl)phenyl]titanium.
[0077] Titanocenes may also be compounds represented by the following formula (III).
[0078] [ka]
[0079] In the formula, R 5 and R 6 Each of these independently represents a halogen atom, an aryl group, an aryl halide, and a heterocyclic aryl halide.
[0080] Examples of commercially available titanosene products include JMT-784 (manufactured by Jin Maotai Technology Co., Ltd., Yueyang City).
[0081] Furthermore, secondary photopolymerization initiators also include phenyl disulfide 2-nitrofluorene, butyroin, anisoin ethyl ether, azobisisobutyronitrile, tetramethylthiuram disulfide, etc. Secondary photopolymerization initiators may be used individually or in combination of two or more.
[0082] When the curable resin composition contains a second photopolymerization initiator, the content of the second photopolymerization initiator in the curable resin composition may be, for example, 0.1 parts by mass or more and 3 parts by mass or less, preferably 0.2 parts by mass or more and 1 part by mass or less, per 100 parts by mass of the total amount of carboxyl group-containing urethane resin. Furthermore, the mass-based content ratio of the second photopolymerization initiator to the photopolymerization initiator containing phosphorus atoms in the curable resin composition may be, for example, 0.03 or more and 0.1 or less, preferably 0.05 or more and 0.08 or less. If the content is within the above range, the curability of the curable resin composition will be improved, and the resolution will also be even better.
[0083] The curable resin composition may contain at least one epoxy compound. The epoxy compound may be an epoxy resin and may be included in the curable resin composition as a thermosetting resin. Specific examples of epoxy compounds include, for example, bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, brominated bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, N-glycidyl type epoxy resin, bisphenol A novolac type epoxy resin, bixylenol type epoxy resin, biphenol type epoxy resin, chelate type epoxy resin, glyoxal type epoxy resin, amino group-containing epoxy resin, rubber-modified epoxy resin, dicyclopentadiene phenolic type epoxy resin, diglycidyl phthalate resin, heterocyclic epoxy resin, tetraglycidyl xylenoylethane resin, silicone-modified epoxy resin, ε-caprolactone-modified epoxy resin, and the like. The epoxy resin may be used alone or in combination of two or more types.
[0084] The epoxy equivalent of the epoxy compound may be, for example, 100 g / eq. to 1500 g / eq., preferably 200 g / eq. to 1200 g / eq., or 400 g / eq. to 1000 g / eq., 800 g / eq. or less, or 600 g / eq. or less. When the epoxy equivalent of the epoxy compound is within the above range, corner cracks during thermal cycling tend to be suppressed more effectively.
[0085] The epoxy compound content in the curable resin composition may be, for example, 5 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the total solid content of the carboxyl group-containing resin, preferably 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more, and preferably 80 parts by mass or less, 60 parts by mass or less, 40 parts by mass or less, or 35 parts by mass or less. If the content is within the above range, the solder heat resistance of the cured product will be better, and the various properties when used as a solder resist for printed circuit boards, especially the insulation reliability, will also be better.
[0086] Furthermore, the epoxy compound content in the curable resin composition may be, for example, 1% by mass or more and 20% by mass or less, preferably 2% by mass or more, 3% by mass or more, or 4% by mass or more, and preferably 15% by mass or less, 10% by mass or less, 7% by mass or less, or 6% by mass or less, based on the total solid content of the curable resin composition. If the content is within the above range, the solder heat resistance of the cured product will be better, and the various properties when used as a solder resist for printed circuit boards, especially the insulation reliability, will also be better.
[0087] The curable resin composition may further contain other thermosetting resins in addition to the epoxy compound. Examples of other thermosetting resins include well-known and commonly used ones such as isocyanate compounds, blocked isocyanate compounds, amino resins, maleimide compounds, benzoxazine resins, carbodiimide resins, cyclocarbonate compounds, oxetane compounds, and episulfide resins. The other thermosetting resins may be used individually or in combination of two or more.
[0088] The curable resin composition may further contain a thermosetting accelerator. By including a thermosetting accelerator, the thermosetting reaction of the thermosetting resin can be accelerated, and properties such as adhesion, chemical resistance, and heat resistance can be further improved. Examples of such thermosetting accelerators include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine derivatives such as adipic acid dihydrazide and sebacate acid dihydrazide; and phosphorus compounds such as triphenylphosphine. Examples of commercially available products include 2E4MZ, 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, and 2P4MHZ (all trade names for imidazole compounds) manufactured by Shikoku Chemicals, Inc., and U-CAT(registered trademark)3503N and U-CAT3502T (both trade names for blocked isocyanate compounds of dimethylamine), DBU, DBN, U-CATSA102, and U-CAT5002 (all bicyclic amidine compounds and their salts) manufactured by Sunapro Co., Ltd. Furthermore, s-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2-vinyl-2,4-diamino-s-triazine, 2-vinyl-4,6-diamino-s-triazine isocyanuric acid adduct, and 2,4-diamino-6-methacryloyloxyethyl-s-triazine isocyanuric acid adduct may also be used, and preferably these compounds that also function as adhesion promoters may be used in combination with the thermosetting accelerator. The thermosetting accelerator may be used alone or in combination of two or more types.From the viewpoint of suppressing corner cracks during thermal cycling, the thermosetting accelerator may contain at least one selected from the group consisting of imidazole derivatives and amine compounds, and may contain at least an amine compound (e.g., dicyandiamide).
[0089] The content of the thermosetting accelerator in the curable resin composition may be, for example, 0.1 parts by mass or more and 20 parts by mass or less, preferably 0.5 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the total amount of thermosetting resin containing the epoxy compound.
[0090] The curable resin composition may contain at least one white pigment and may also contain at least one titanium dioxide. Titanium dioxide may be included in the curable resin composition as a white pigment. As titanium dioxide, those produced by the sulfuric acid method, the chlorine method, etc., rutile-type titanium dioxide, anatase-type titanium dioxide, or titanium dioxide that has been surface-treated with a hydrated metal oxide or an organic compound can be used. Among these titanium dioxides, rutile-type titanium dioxide is preferred from the viewpoint of forming a stable photosensitive resin layer. As rutile-type titanium dioxide, known rutile-type products can be used. Specifically, TR-600, TR-700, TR-750, TR-840 from Fuji Titanium Industries Co., Ltd., Typeque R-550, R-580, R-630, R-820, CR-50, CR-58, CR-60, CR-90 from Ishihara Industries Co., Ltd., and KR-270, KR-310, KR-380 from Titanium Industries Co., Ltd. can be used. Titanium dioxide may be used alone or in combination of two or more types.
[0091] While the particle size of titanium dioxide is not particularly limited, from the viewpoint of resolution, reflectance, and insulation reliability, it is preferable that the average particle size is in the range of 10 nm to 1 μm. In this specification, the average particle size refers to the cumulative average particle size of 50% (D) when the particle size distribution is prepared on a volume basis. 50This refers to the value of the particle size distribution (PDI), which can be determined by a laser diffraction particle size distribution analyzer or a dynamic light scattering analyzer. Examples of laser diffraction analyzers include the Microtrac MT3300EXII manufactured by Microtrac-Bell Corporation, and examples of dynamic light scattering analyzers include the Nanotrac Wave II UT151 manufactured by Microtrac-Bell Corporation.
[0092] The content of the white pigment in the curable resin composition may be adjusted as appropriate to obtain the desired reflectance. The content of the white pigment in the curable resin composition may be, for example, 20% by mass or more and 90% by mass or less, preferably 40% by mass or more, 60% by mass or more, 65% by mass or more, 68% by mass or more, or 70% by mass or more, and preferably 85% by mass or less, 80% by mass or less, or 75% by mass or less, based on the total solid content of the curable resin composition.
[0093] Furthermore, the content of the white pigment in the curable resin composition may be, for example, 300 parts by mass or more and 600 parts by mass or less per 100 parts by mass of the total solid content of the carboxyl group-containing resin, preferably 360 parts by mass or more, or 400 parts by mass or more, and preferably 500 parts by mass or less, or 460 parts by mass or less. When the content of the white pigment is within the above range, the occurrence of corner cracks tends to be suppressed more effectively.
[0094] The curable resin composition may contain white pigments other than titanium dioxide. Examples of white pigments other than titanium dioxide include zinc oxide, magnesium oxide, zirconium oxide, aluminum oxide, and zinc sulfide. These white pigments may be used individually or in combination of two or more. When the curable resin composition contains white pigments other than titanium dioxide, the titanium dioxide content in the white pigment may be, for example, 80% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more.
[0095] The curable resin composition may further contain at least one photopolymerizable compound. The photopolymerizable compound may be any compound having an ethylenically unsaturated double bond. Examples of photopolymerizable compounds include well-known and conventional photopolymerizable polymers, photopolymerizable oligomers, and photopolymerizable monomers, and mixtures thereof may also be used. Because the photopolymerizable compound has an ethylenically unsaturated double bond, it helps to insolubilize the cured product cured by active energy ray irradiation in an alkaline aqueous solution.
[0096] Examples of photopolymerizable oligomers include unsaturated polyester oligomers and (meth)acrylate oligomers. Examples of (meth)acrylate oligomers include epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol-type epoxy (meth)acrylate, as well as urethane (meth)acrylate, epoxy urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and polybutadiene-modified (meth)acrylate. Examples of photopolymerizable monomers include alkyl(meth)acrylates such as 2-ethylhexyl(meth)acrylate and cyclohexyl(meth)acrylate; hydroxyalkyl(meth)acrylates such as 2-hydroxyethyl(meth)acrylate and 2-hydroxypropyl(meth)acrylate; mono- or di(meth)acrylates of alkylene oxide derivatives such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; hexanediol, trimethylolpropane, pentaerythritol, ditrimethylolpropane, dipentaerythritol, and Examples include polyhydric (meth)acrylates derived from polyhydric alcohols such as hydroxyethyl isocyanurate or their ethylene oxide or propylene oxide adducts; (meth)acrylates derived from ethylene oxide or propylene oxide adducts of phenols such as phenoxyethyl (meth)acrylate and polyethoxydi(meth)acrylate of bisphenol A; (meth)acrylates derived from glycidyl ethers such as glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and melamine (meth)acrylate. Photopolymerizable compounds may be used individually or in combination of two or more.
[0097] The photopolymerizable compound may contain at least one selected from the group consisting of polyhydric (meth)acrylates of polyhydric alcohols or their ethylene oxide or propylene oxide adducts (hereinafter also referred to as alkylene oxide adducts), and (meth)acrylates of alkylene oxide adducts of phenols, and may contain at least one selected from the group consisting of polyhydric (meth)acrylates of alkylene oxide adducts of polyhydric alcohols, and polyhydric (meth)acrylates of alkylene oxide adducts of polyhydric phenols. By including a specific compound as the photopolymerizable compound, the occurrence of corner cracks can be suppressed more effectively.
[0098] The content of the photopolymerizable compound in the curable resin composition may be, for example, 5 parts by mass or more and 100 parts by mass or less, preferably 10 parts by mass or more, or 20 parts by mass or more, or 70 parts by mass or less, or 40 parts by mass or less, based on 100 parts by mass of the total solid content of the carboxyl group-containing resin. If the content is within the above range, the resolution and the strength of the cured product can be further improved.
[0099] The curable resin composition may contain, as a photopolymerizable compound, polyhydric alcohols or polyhydric (meth)acrylates of alkylene oxide adducts thereof, and polyhydric (meth)acrylates of alkylene oxide adducts of polyhydric phenols. By including a specific combination of compounds as the photopolymerizable compound, the occurrence of corner cracks can be suppressed more effectively. When the curable resin composition contains polyhydric alcohols or polyhydric (meth)acrylates of alkylene oxide adducts thereof, and polyhydric (meth)acrylates of alkylene oxide adducts of polyhydric phenols, the content ratio of polyhydric (meth)acrylates of alkylene oxide adducts of polyhydric phenols to polyhydric alcohols or polyhydric (meth)acrylates thereof may be, for example, 0.5 to 3 by mass, and preferably 1 to 2.
[0100] The curable resin composition may further contain other additives besides the components mentioned above. Examples of additives include inorganic fillers such as barium sulfate, silica, and talc; organic fillers such as silicone powder, nylon powder, and fluorine powder; well-known and conventional thickeners such as fine silica, organic bentonite, and montmorillonite; compounds having polar groups such as carboxyl groups, hydroxyl groups, and acid esters; copolymers containing acid groups; wetting and dispersing agents such as hydroxyl group-containing polycarboxylic acid esters; defoaming agents and / or leveling agents such as silicone-based, fluorine-based, and polymer-based agents; and fiber reinforcing materials such as glass fibers, carbon fibers, and boron nitride fibers. Furthermore, if necessary, it may also contain well-known and conventional antioxidants, adhesion promoters, ultraviolet absorbers, polymerization inhibitors, silane coupling agents such as imidazole-based, thiazole-based, and triazole-based agents, plasticizers, foaming agents, flame retardants, antistatic agents, anti-aging agents, and antifungal agents.
[0101] The curable resin composition may contain organic solvents as needed for purposes such as composition preparation and viscosity adjustment when applying to substrates, films, etc. The inclusion of organic solvents allows for uniform dissolution or dispersion of the above-mentioned components and adjustment to a viscosity suitable for coating. As organic solvents, known and commonly used organic solvents can be used, such as ketones like methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons like toluene, xylene, and tetramethylbenzene; glycol ethers like cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters like ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, diethylene glycol monoethyl ether acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons like octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These organic solvents may be used individually or in combination of two or more. The content of the organic solvent in the curable resin composition can be appropriately set according to the desired viscosity.
[0102] A curable resin composition can be prepared as follows: After weighing and blending each component, the mixture is pre-mixed in a stirrer, and then dispersed and kneaded in a kneader. Examples of kneaders include bead mills, ball mills, sand mills, three-roll mills, and two-roll mills. Among these, a three-roll mill is preferable to improve dispersibility. Alternatively, the curable resin composition may be obtained by dissolving or dispersing the above-mentioned components using a mixer, such as a disper, kneader, three-roll mill, or bead mill.
[0103] Curable resin compositions are useful for forming pattern layers as permanent coatings on printed circuit boards, and are also useful for forming solder resists, decorative permanent coatings, and the like. Curable resin compositions may be used as dry films or as liquids. When used as liquids, they may be one-component or two-component or more.
[0104] Dry film The curable resin composition can also be in the form of a dry film comprising a first film and a resin layer formed from a dried coating of the curable resin composition laminated on the first film. The first film refers to a film that is at least adhered to the resin layer when laminated onto a substrate so that the resin layer side of the dry film is in contact with it. The first film may be peeled off from the resin layer in a post-lamination process. It is particularly preferable to peel it off from the resin layer in a post-exposure process. When forming a dry film, the curable resin composition may be diluted with an organic solvent as needed to adjust to an appropriate viscosity. The dry film can be obtained by applying the curable resin composition to the first film to a uniform thickness using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, etc., and drying it at a temperature of 50°C to 130°C for 1 to 30 minutes to form a dried coating. There are no particular restrictions on the coating film thickness, but generally, the film thickness after drying may be, for example, 10 μm to 300 μm, and preferably appropriately selected within the range of 20 μm to 200 μm.
[0105] The first film can be any known film without particular limitations, and for example, films made of thermoplastic resins such as polyester films (polyethylene terephthalate, polyethylene naphthalate, etc.), polyimide films, polyamide-imide films, polypropylene films, and polystyrene films can be suitably used. Among these, polyester films are preferred from the viewpoint of heat resistance, mechanical strength, and handling. Laminates of these films can also be used as the first film. From the viewpoint of improving mechanical strength, films made of thermoplastic resins are preferably films that are stretched in one or two axes. The thickness of the first film is not particularly limited and can be, for example, 10 μm or more and 150 μm or less.
[0106] It is preferable to form a resin layer consisting of a dried coating of a curable resin composition on the first film, and then to laminate a peelable second film onto the surface of the resin layer for purposes such as preventing dust from adhering to the surface of the resin layer. The second film is a film that is peeled off from the resin layer before lamination when laminating the dry film onto the substrate so that the resin layer side of the dry film is in contact with it. As the second film, for example, polyethylene film, polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc., should be such that the adhesive force between the resin layer and the second film is less than the adhesive force between the resin layer and the first film when the second film is peeled off. The thickness of the second film is not particularly limited and can be, for example, 10 μm or more and 150 μm or less.
[0107] In one embodiment, the present invention may include electronic components comprising a cured product. Here, "electronic components" means components used in electronic circuits, and includes active components such as printed circuit boards, especially flexible printed circuit boards, transistors, light-emitting diodes, and laser diodes, as well as passive components such as resistors, capacitors, inductors, and connectors. The cured product of the curable resin composition is suitable as a solder resist for these components. [Examples]
[0108] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0109] Synthesis Example 1: Resin Varnish A-1 In a reaction vessel equipped with a stirrer, thermometer, and condenser, 2400 g (3 moles) of polycarbonate diol derived from 1,5-pentanediol and 1,6-hexanediol (manufactured by Asahi Kasei Corporation, TJ5650J, number average molecular weight 800), 603 g (4.5 moles) of dimethylolpropionic acid, and 238 g (2.6 moles) of 2-hydroxyethyl acrylate as a monohydroxy compound were added. Next, 1887 g (8.5 moles) of isophorone diisocyanate was added as the polyisocyanate, and the mixture was heated to 60°C while stirring, then stopped. When the temperature in the reaction vessel began to decrease, it was heated again and stirring continued at 80°C, and the absorption spectrum of the isocyanate group (2280 cm⁻¹) was measured using infrared absorption spectroscopy. -1 The reaction was terminated after confirming that the ) had disappeared. Carbitol acetate was added to bring the solid content to 50% by mass to obtain resin varnish A-1 containing a carboxyl group-containing urethane resin with a polycarbonate skeleton. The solid had an acid value of 50 mgKOH / g and a weight-average molecular weight Mw of approximately 17,000.
[0110] Synthesis Example 2: Resin Varnish A-2 In a reaction vessel equipped with a stirrer, thermometer, and condenser, 2000 g (2.5 mol) of polycarbonate diol derived from 1,5-pentanediol and 1,6-hexanediol (manufactured by Asahi Kasei Corporation, TJ5650J, number average molecular weight 800), 670 g (5 mol) of dimethylolpropionic acid, and 238 g (2.6 mol) of 2-hydroxyethyl acrylate as a monohydroxy compound were added. Next, 1787 g (8.5 mol) of trimethylhexamethylene diisocyanate was added as the polyisocyanate, and the mixture was heated to 60°C while stirring, then stopped. When the temperature in the reaction vessel began to decrease, it was heated again and stirring was continued at 80°C, and the absorption spectrum of the isocyanate group (2280 cm⁻¹) was measured using infrared absorption spectroscopy.-1 The reaction was terminated after confirming that the ) had disappeared. Carbitol acetate was added to bring the solid content to 50% by mass to obtain resin varnish A-2 containing a carboxyl group-containing urethane resin with a polycarbonate skeleton. The solid had an acid value of 70 mgKOH / g and a weight-average molecular weight Mw of approximately 15,000.
[0111] Synthesis Example 3: Resin Varnish A-3 In a flask equipped with a thermometer, stirrer, dropping funnel, and reflux condenser, 325.0 g of dipropylene glycol monomethyl ether as a solvent was heated to 110°C. A mixture of 174.0 g of methacrylic acid, 174.0 g of ε-caprolactone-modified methacrylic acid (average molecular weight 314), 77.0 g of methyl methacrylate, 222.0 g of dipropylene glycol monomethyl ether, and 12.0 g of t-butyl peroxy 2-ethylhexanoate (product name: Perbutyl O, manufactured by Nippon Oil & Fats Co., Ltd.) as a polymerization catalyst was added dropwise over 3 hours. The mixture was then stirred at 110°C for another 3 hours to deactivate the polymerization catalyst and obtain a resin solution. After cooling this resin solution, 289.0 g of cyclomer M100 (manufactured by Daicel Corporation), 3.0 g of triphenylphosphine, and 1.3 g of hydroquinone monomethyl ether were added. The mixture was heated to 100°C and stirred to carry out the ring-opening addition reaction of the epoxy group, thereby completing the reaction. Dipropylene glycol monomethyl ether was added to bring the solid content to 50% by mass to obtain resin varnish A-3 containing a carboxyl group-containing resin without urethane bonds. The solid content had an acid value of 79.8 mg KOH / g and a weight-average molecular weight Mw of approximately 18,000.
[0112] Synthesis Example 4: Resin Varnish A-4 220 g of cresol novolac type epoxy resin (DIC Corporation, EPICLON N-695, epoxy equivalent: 220 g / eq.) was placed in a four-necked flask equipped with a stirrer and reflux condenser, and 214 g of carbitol acetate was added and heated until dissolved. Next, 0.1 g of hydroquinone was added as a polymerization inhibitor and 2.0 g of dimethylbenzylamine was added as a reaction catalyst. This mixture was heated to a temperature of 95°C to 105°C, and 72 g of acrylic acid was gradually added dropwise, and the reaction was allowed to proceed for 16 hours. The reaction product was cooled to a temperature of 80°C to 90°C, 106 g of tetrahydrophthalic anhydride was added, and the reaction was allowed to proceed for 8 hours to complete the reaction. After cooling, carbitol acetate was added to bring the solid content to 50% by mass to obtain resin varnish A-4 containing a carboxyl group-containing resin without urethane bonds. The solid content had an acid value of 100 mg KOH / g and a weight-average molecular weight Mw of approximately 3,500.
[0113] Examples 1 to 7 and Comparative Examples 1 to 7 Using the resin varnish described above as the carboxyl group-containing resin, various components shown in Table 1 were blended in the indicated proportions (parts by mass). After pre-mixing with a stirrer, the mixture was kneaded in a three-roll mill to prepare a curable resin composition. Unless otherwise specified, the values in Table 1 represent the solid content in parts by mass. "-" indicates that the component was not added.
[0114] [Table 1]
[0115] The details of the components in Table 1 are as follows: Photopolymerization initiator Omnirad TPO N: Manufactured by IGMRESINSB.V.; Monoacylphosphine oxide-based photopolymerization initiator • Omnirad 819: Manufactured by IGMRESINS B.V.; Bisacylphosphine oxide-based photopolymerization initiator • Irgacure OXE-04: Manufactured by BASF Japan Ltd.; Oxime ester-based photopolymerization initiator ·JMT-784: Manufactured by Yueyang Jin Maotai Technology Co., Ltd.; Titanocene photopolymerization initiator thermosetting resin • YX7400N: Manufactured by Mitsubishi Chemical Corporation; epoxy equivalent 440 g / eq. • YD-134: Manufactured by Nippon Steel Chemical & Material Co., Ltd.; epoxy equivalent 250g / eq. photopolymerizable compound • Arronix M-321: Manufactured by Toagosei Co., Ltd.; Propoxylated trimethylolpropane triacrylate • BPE-900: Manufactured by Shin-Nakamura Chemical Industry Co., Ltd.; Ethoxylated bisphenol A dimethacrylate • EBECRYL270: Manufactured by Daicel Ornex Co., Ltd.; carboxyl group-free urethane acrylate Titanium oxide • CR-Super70: Manufactured by Ishihara Sangyo Co., Ltd.; Rutile-type titanium oxide Thermosetting accelerator • DICY7: Manufactured by Mitsubishi Chemical Corporation; dicyandiamide additives • Floren AC300VF: Manufactured by Kyoeisha Chemical Co., Ltd.; Antifoaming agent • BYK-180: Manufactured by Big Chemie Japan Co., Ltd.; Wetting and dispersing agent
[0116] Preparation of a cured material for measuring elastic modulus The curable resin composition obtained above was screen printed onto a copper foil-covered glass epoxy substrate to a thickness of 60 μm, and dried at 80°C for 30 minutes. Next, using an exposure machine (680GW: manufactured by Oak Manufacturing Co., Ltd.), an exposure mask capable of forming a 5 mm x 40 mm strip pattern was used to expose the material at 700 mJ / cm². 2The substrate was exposed to light. Subsequently, it was developed at 30°C in a 1% by mass aqueous sodium carbonate solution for 70 seconds to obtain a 5 mm × 40 mm strip pattern. Next, it was heat-cured at 150°C for 60 minutes to obtain a substrate with a cured coating. The obtained coated substrate was etched with ferric chloride to remove copper foil, and then dried at 150°C for 10 minutes to obtain a strip-shaped cured product (0). The obtained coated substrate was also heated on a hot plate at 280°C for 5 minutes, etched with ferric chloride to remove copper foil, and then dried at 150°C for 10 minutes to obtain a strip-shaped cured product (1) after heat treatment. Furthermore, the strip-shaped cured product (1) was immersed in 50 mL of propylene glycol monomethyl ether at 25°C for 5 minutes, and then dried at 150°C for 10 minutes to obtain a strip-shaped cured product (2) after washing.
[0117] Measurement of elastic modulus The strip-shaped hardened material obtained above was measured using a dynamic viscoelasticity measuring device (RSA-G2: manufactured by T.A. Instrument Japan Co., Ltd.) in tensile mode. Tensile tests were performed with a chuck distance of 10 mm and a speed of 1 mm / min, and the modulus of elasticity (GPa) at 25°C was measured. The results are shown in Table 1. The modulus of elasticity values are calculated from the measured values, and the values are rounded to two decimal places. Next, the modulus ratio was calculated based on the measured modulus of elasticity.
[0118] Thermal cycling test The curable resin composition obtained above was screen printed onto a glass substrate (Eagle XG) to a thickness of 60 μm and dried at 80°C for 30 minutes. Next, using an exposure mask capable of forming 500 rectangular openings measuring 350 μm × 450 μm at 2 mm intervals, an exposure of 700 mJ / cm² was performed using an exposure machine (680GW: manufactured by Oak Manufacturing Co., Ltd.). 2The substrate was exposed to light. Subsequently, development was performed at 30°C in a 1% by mass aqueous sodium carbonate solution for 70 seconds to form a pattern with 500 rectangular openings measuring 350 μm × 450 μm at 2 mm intervals. Next, the substrate was heat-cured at 150°C for 60 minutes to obtain a substrate with a cured coating. The obtained substrate with a cured coating was heat-treated on a hot plate at 280°C for 5 minutes. After immersion in 50 mL of propylene glycol monomethyl ether at 25°C for 5 minutes, it was dried at 150°C for 10 minutes to obtain a substrate with a cured product after washing.
[0119] After cleaning, the cured substrate was prepared by potting the opening with silicone encapsulating resin ASP-2010 (manufactured by Shin-Etsu Chemical Co., Ltd.) in a semi-circular shape with a diameter of 2 mm. A heat curing treatment was then performed at 100°C for 2 hours and at 150°C for 4 hours to form a cured silicone resin product on the opening, which was then used as an evaluation sample.
[0120] The evaluation samples obtained as described above were subjected to a thermal cycling test using a constant temperature bath ARS-0680-5 (manufactured by ESPEC Corporation), with a holding time of 30 minutes and a temperature change time of 30 minutes, repeating the cycle between -40°C and 100°C 500 or 1000 times. After the test, the coating film was observed at 300x magnification using an optical microscope (digital microscope; VHX-8000: manufactured by KEYENCE Corporation). For the evaluation samples after 500 thermal cycling cycles, the corner crack occurrence rate at 500 openings was calculated. In addition, the delamination rate of the silicone resin was calculated for the evaluation samples after 500 and 1000 thermal cycling cycles, respectively. The evaluation criteria for the corner crack occurrence rate are as follows. The results are shown in Table 1.
[0121] Evaluation Criteria A: The incidence of corner cracks was less than 1%. B: The incidence of corner cracks was between 1% and 3%. C: The incidence of corner cracks was 3% or higher.
[0122] Furthermore, the evaluation criteria for the delamination rate of silicone resin, which serves as an indicator of silicone resin curability, are as follows. The results are shown in Table 1.
[0123] A: The incidence of peeling was less than 1%. B: The frequency of peeling was between 1% and 3%. C: The incidence of peeling was 3% or higher.
[0124] As shown in Table 1, in cured products formed from a curable resin composition containing a carboxyl group-containing urethane resin, a photopolymerization initiator containing a phosphorus atom, an epoxy compound, and titanium dioxide, and having a predetermined elastic modulus ratio, the inhibition of silicone resin curing is suppressed, and the occurrence of corner cracks during thermal cycling is suppressed.
Claims
1. A cured product formed from a curable resin composition comprising a carboxyl group-containing urethane resin, a first photopolymerization initiator containing a phosphorus atom, an epoxy compound, and titanium dioxide, The elastic modulus G of the heat-treated cured material obtained by heat-treating the aforementioned cured material at 280°C for 5 minutes, measured by dynamic viscoelasticity at 25°C. 1 In response to, The elastic modulus G of the washed cured product obtained by immersing the heat-treated cured product in propylene glycol monomethyl ether at 25°C for 5 minutes and then drying it was determined by dynamic viscoelasticity measurement at 25°C. 2 Ratio G 2 / G 1 A cured product in which the ratio is between 1.05 and 1.
20.
2. The cured product according to claim 1, wherein the concentration of the first photopolymerization initiator in acetonitrile extracted from 50 mg of the heat-treated cured product into 10 mL of acetonitrile at 25°C for 10 minutes is 0.1 ppm or more and 30 ppm or less.
3. The cured product according to claim 1, wherein the carboxyl group-containing urethane resin includes a polycarbonate skeleton.
4. The curable resin composition comprises a first photopolymerization initiator containing an acylphosphine oxide-based photopolymerization initiator and a second photopolymerization initiator containing at least one selected from the group consisting of oxime ester-based photopolymerization initiators and titanocene-based photopolymerization initiators, as described in claim 1.
5. The cured product according to claim 1, wherein the epoxy compound has an epoxy equivalent of 400 g / eq. to 1000 g / eq.
6. The cured product according to claim 1, wherein the titanium oxide content is 65% by mass or more.
7. An electronic component comprising a cured product according to any one of claims 1 to 6.
Citation Information
Patent Citations
Photosensitive thermosetting resin composition, smoothed printed wiring board coated with resist film and method for manufacturing the same
JP2007249148A
White alkali-developable photocurable and thermosetting solder resist composition, and metal-base circuit substrate using the same
JP2009194222A
Flame-retardant solder resist composition and flexible wiring board which is obtained using same
WO2011062053A1